Enhancing Attention and Focus in Children with ADHD Through Structured Sensory Play Based on Project-Based Learning - Saragih, Yenny Vitasari; Azizah, Nur (Papanda Publisher, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) significantly impacts early childhood learning, with children demonstrating difficulties in maintaining attention and focus during educational activities. This study investigated the effectiveness of structured sensory play based on Project-Based Learning (PjBL) in enhancing attention and focus among children with ADHD in kindergarten settings. An action research design following Kemmis and McTaggart's spiral model was implemented across two cycles with 17 children aged 4-5 years in Group A kindergarten, including one formally diagnosed ADHD participant. Each cycle comprised two sessions incorporating forest-themed projects with structured sensory activities. Data collection utilized structured observation checklists measuring attention duration, eye contact, instruction following, activity engagement, behavioral regulation, and task completion. Assessment employed a 4-point rating scale with success criteria established at 76-100% achievement levels. Significant improvements were observed across all participants. Pre-cycle assessment showed 47% of children in the